Systematic Literature Review: Mathematical Connections in Solving Contextual Mathematics Problems - Syafirda Aulia; Anis Farida Jamil; Arif Hidayatul Khusna (Journal of Teaching and Learning Mathematics, 2026)
Mathematical connection skills are important in supporting students in solving contextual mathematical problems. However, several studies show that connection skills are still an obstacle for junior high school students. This study aims to analyze junior high school students' mathematical connection skills in solving contextual problems through a Systematic Literature Review (SLR) approach. This study reviewed research articles published between 2019 and 2025 and obtained through the Google Scholar database. Based on the inclusion criteria, eight articles were selected for systematic analysis. The results showed that junior high school students' mathematical connection skills were in the low to moderate category, particularly in relating mathematical concepts to everyday contexts and connecting between mathematical topics. Students with high mathematical abilities were able to build conceptual and procedural connections, but still experienced difficulties in the representational aspect. Meanwhile, students with moderate and low mathematical abilities experience more complex difficulties in connecting contextual information with mathematical concepts. These findings indicate the importance of applying contextual learning that emphasizes the interrelationship between concepts and the use of various representations to improve the quality of junior high school students' mathematical problem solving.